Alyson Crist: capstone - Crist, Alyson, artist (Colorado State University. Libraries, 2016)
The artist's statement: By challenging the division between the realm of memory and the realm of practice, I have attempted to create work with a fascination of content and an adamant attitude towards conceptual art. Creating fabric allows me to explore my personal vision of memory and projection; through layering and repetition of line and form, I can visually create my personal thought process. Inspired by artists such as Lenore Tawney and her intersection of lines in space in tapestry weaving, I have created work that utilizes this style, as well as the grid and curves. My weaving shadows historical techniques and forms, with a play of functional craftsmanship, inspired by relic textiles.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: fibers